FREQUENCY AND TYPES OF ANEMIA IN AN ANTENATAL CLINIC IN THE THIRD TRIMESTER OF PREGNANCY: Anaemia in the Third Trimester of Pregnancy - Khalil, Adiba Akhtar; Jabbar, Tahira; Akhtar, Shahida; Mohyuddin, Sobia (Pakistan Armed Forces Medical Journal, 2007)
Objective: To determine the frequency and the types of anemia in a specific sample of patients reporting to Combined Military Hospital, Rawalpindi.Design and Setting: A descriptive study with retrospective data was conducted in outdoor patients department of Combined Military Hospital, Rawalpindi by screening/testing haemoglobin and haematocrit in the third trimester of pregnancy.Patients and Methods: Five hundred patients that reported to outdoor patient department of Combined Military Hospital, Rawalpindi from July 2002 to January 2003, were selected for study according to the inclusion and exclusion criteria by convenience sampling. Study was carried out on automated electronic cell counters and chemical analyzers. Any abnormal results in routine investigations were followed up. Inclusion criteria was educated women with at least a high school degree in their third trimester with age ranging between 20 to 30 years, gravidity between 1 to 3 and birth spacing of at least 2 years.Results: The significant out come of the study was that iron deficiency anemia exists substantially in this socioeconomic group (educated middle class). Out of the total 500 cases, 241 (48.2%) were found to be anemic, according to the severity was 39.8% mild, 7.6% moderate and 0.8% severe anemia. The mean + SD haemoglobin was 10.3 ± 0.3 g/dL for mild, 8.9 ± 0.41 g/dL for moderate and 6.8 ± 0.22 g/dL for severe anemia. Seventeen patients out of the original sample were lost to follow up. The major categories of anemia to effect the study sample were iron deficiency anemia and beta thalassaemia trait. The percentages obtained were 41.6% and 4.8% respectively.Conclusion: Iron deficiency is quite frequent during third trimester of pregnancy is our study population. A comprehensive research in our country is needed on how to improve existing iron supplementation programs and the overall health care and nutritional status of women before they enter their reproductive years.